Simulation and characterization of PZT thin film capacitors for MMIC applications / Nor Fazlina Mohd Lazim - Mohd Lazim, Nor Fazlina (2008)
This thesis reports a research carried out to simulate and characterize lead zirconate titanate (PZT) thin film capacitors for monolithic microwave integrated circuit (MMIC) applications. The PZT thin film capacitor was modeled as thin film microstrip structure (TFMS) which shares the same configurations as a conventional microstrip. The capacitor was simulated using electromagnetic simulator Sonnet to determine the important characteristics of 50 Ω line width, and PZT thickness and permittivity. For a 50 Ω line, the width obtained is merely 300 nm for a PZT of εr = 100. This results in size reduction of more than fifty times compared to conventional MMIC. Various capacitor areas were also simulated and the effects of parameters such as εr, d and A on the capacitance values were investigated. The capacitance is simulated for film thicknesses ranging from 0.1 to 0.3 µm2 and εr from 100 to 1000. The capacitor electrode areas were changed from 3 x 3 µm2to 50 x 50 µm2over the frequency range of 1 - 100 GHz. In order to prove the feasibility of this new idea, capacitors utilizing PZT thin films were deposited on Pt/Ti/SiO2-coated Si substrates. The films were grown by RF sputtering, and platinum and gold electrodes were delineated on the samples using electron beam lithography. For an electrode area of 50 x 50 µm2, capacitance values of 10 pF were obtained at frequencies up to 20 GHz. Suitable de-embedding of S-parameters using Cascade microwave probes revealed films with εr of the order of300 to 500. To the author’s knowledge this project constitutes the first work on PZT thin film capacitors for MMIC applications.